Assessment of economic security of enterprises: Theoretical and methodological aspects - Svitlana Shynkar; Zoriana Gontar; Mariya Dubyna; Daria Nasypaiko; Mariya Fleychuk (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The main objective of the study is to formulate a new approach of assessing economic security for industrial enterprises, indicating a different approach from existing ones, to allow for the very specifics of economic activity, and to allow the use of qualitative and quantitative indicators. We justified that the effectiveness of ensuring the economic security for industrial enterprises is determined by the quality of the information basis for the actions of security entities. A methodological approach is proposed that provides for the determination of the security level at three levels: "indicator - functional component - financial indicator" and allows to obtain reliable information about the economic security of oil and gas, engineering and food industries by taking into account the specifics of their economic activities.
Keywords: B49; C10; C13; D21; M20; M41; 650; security; economic security; enterprise; assessment of economic security; assessment